Ab initio Investigation of the Structural and Electronic Properties of Alkaline Earth Metal - TiO2 Natural Polymorphs - Jane Kathure Mbae; Zipporah Wanjiku Muthui (Advances in Materials Science and Engineering)
Titanium (IV) oxide (TiO2) has gained much attention due to its application in technologies such as optoelectronics, electronics, sensors, photocatalysts, and sustainable energy generation. However, its optical absorption falls in the ultraviolet part of the electromagnetic spectrum, resulting in a low absorption ratio of solar light. In addition, rapid electron-hole recombination limits its photocatalytic activity. To extend the application range of TiO2, the structural and chemical properties can be modified by adding various dopants to tune its electronic structure for applications within a wider range of the solar energy spectrum and ideally extend towards the visible region, which forms the dominant part of the solar energy spectrum. In this study, the structural and electronic properties of three polymorphs of TiO2 have been studied using density functional theory (DFT) as implemented in the Quantum ESPRESSO simulation package. The exchange-correlation potential has been treated with the generalised gradient approximation (GGA). Cationic substitution with non-toxic alkaline earth metal dopants Mg and Ca has been carried out with the aim of modifying the electronic structure of the polymorphs of TiO2. On 1–4% Mg and Ca cationic substitution, there is a slight expansion of the optimal unit cell volume and modulation of the band gap energy by raising the valence band maximum to higher energies. In addition, dopant inter and intra-band states are observed.